Exposure to Mycobacterium avium Decreases the Protective Effect of the DNA Vaccine pVAXhsp65 Against Mycobacterium tuberculosis-Induced Inflammation of the Pulmonary Parenchyma - Martins, D. R. [UNESP]; Pelizon, A. C. [UNESP]; Zorzella-Pezavento, S. F. G. [UNESP]; Seger, J. [UNESP]; Santos Junior, R. R. [UNESP]; Fonseca, D. M. [UNESP]; Justulin, L. A.; Silva, C. L. [UNESP]; Sartori, Alexandrina [UNESP] (Wiley-Blackwell, 2011)
This work investigated the effect of previous Mycobacterium avium exposure on the protective ability of the DNA vaccine pVAXhsp65 against inflammation in the pulmonary parenchyma. BALB/c mice were presensitized with heat-killed M. avium and then immunized with three doses of pVAXhsp65 prior to challenge with Mycobacterium tuberculosis. M. avium sensitization induced high levels of spontaneous IL-5 production that were concomitant with a positive delayed-type hypersensitivity reaction; antigen-specific IFN-gamma production was also observed upon splenocyte stimulation. Prior exposure to M. avium resulted in altered cytokine and antibody production induced by immunization with pVAXhsp65; instead of a Th1 response, vaccinated mice previously exposed to M. avium developed a strong Th2 response. This switch to a Th2 response coincided with the loss of the anti-inflammatory effect of pVAXhsp65 vaccination previously observed in the pulmonary parenchyma of mice infected with M. tuberculosis. These results suggest that exposure to environmental mycobacteria can modulate immune responses induced by mycobacterial vaccines other than bacillus Calmette-Guerin.